2020
DOI: 10.1016/j.aop.2020.168097
|View full text |Cite
|
Sign up to set email alerts
|

Generalized criteria of symmetry breaking. A strategy for quantum time crystals

Abstract: The aim of this paper is to propose a criterion of spontaneous symmetry breaking that makes reference to the properties of pure phases defined by a translationally invariant state. By avoiding any reference to the ground state, at the basis of the standard approach, this criterion applies to a wider class of models. An interesting application is the breaking of time translations. Indeed, we discuss explicit theoretical models which exhibit the prototypical features of quantum time crystals, without the need of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…In fact, the derivation of Eq. ( 9) of [53], which leads to Equation (23), tacitly assumed translation invariance of these quantities. The recent preprint [38] reported that the lack of translation covariance of local order parameters can yield breakdown of (24) for a translation invariant vacuum state of some simple quantum field model.…”
Section: A Summary Of the Statement Bymentioning
confidence: 99%
See 3 more Smart Citations
“…In fact, the derivation of Eq. ( 9) of [53], which leads to Equation (23), tacitly assumed translation invariance of these quantities. The recent preprint [38] reported that the lack of translation covariance of local order parameters can yield breakdown of (24) for a translation invariant vacuum state of some simple quantum field model.…”
Section: A Summary Of the Statement Bymentioning
confidence: 99%
“…Finite-range Hamiltonians are considered in [54]. The Lieb-Robinson bound estimate [32] for local Hamiltonians is applied to derive (23). It has been known that any finite-range quantum spin lattice model has an approximately inner {α t ∈ Aut(A), t ∈ R}, and that the Lieb-Robinson bound estimate yields an approximately inner time evolution, see [5] [39].…”
Section: B On Watanabe-oshikawa-koma's No-go Statementmentioning
confidence: 99%
See 2 more Smart Citations
“…With the advent of spontaneous symmetry breaking, a mechanism typically appearing in infinitely extended systems, or in any case for systems admitting more than one inequivalent realization (see e.g. [2,3]), the Wigner-Eckart strategy appears to be completely out of use; first because the symmetries of the Hamiltonian may be completely lost at the level of the states. Second, only in special cases the effect of spontaneous symmetry breaking may be considered small and treated by means of a perturbative expansion.…”
Section: Introductionmentioning
confidence: 99%